The Masquelet technique combined with the muscle flap for use in emergency management of acute Gustilo type III trauma of the lower limb with segmental bone loss:Case series. (September 2020) - Deng, Linglong; Yu, Aixi; Qi, Baiwen; Lei, Jun; De Souza, Cristabelle; Zhu, Shaobo; Yu, Li
Abstract: Background: Gustilo-Anderson type III traumas have been described as high-energy injuries with severe bone defects and extensive soft tissue damage, which remain a challenging entity, due to an inherent risk of infection, nonunion and even amputation. The emergency management of such severe trauma presents additional difficulties. Our study attempts to retrospectively evaluate the Masquelet technique combined with the muscle flap for the management of Gustilo type III trauma of the lower limb with segmental bone loss in emergencies and assess key points of success in this technique. Material and methods: From June 2014 to December 2017, 17 patients of Gustilo type IIIA/B/C trauma of lower limb with segmental bone loss, were recruited for our studies. All the cases experienced thorough debridement, stabilization of fracture and antibiotic-impregnated cement spacer insertion. When necessary, muscle flap surgeries were performed immediately. After wound healing, cement spacers were removed, and cancellous bone was filled to repair bone defects. Procedures were performed by two experienced orthopedic surgeons. Results: Among the patients studied, retrograde translocations of the medial head of the gastrocnemius were performed in 5 cases, medial hemimuscular flaps of soleus in 3 cases, and medial head of the gastrocnemius combined with medial hemimuscular flaps of soleus in 4 cases. One patient developed a necrotic soleus flap and was treated with the cross-leg flap. Using a mean 28.2 months of follow-up, results were analyzed radiologically and clinically. Failures (include infection and nonunion) were not noted. And all the patients returned to full weight bearing without pain. According to the Paley fracture healing score, 15 patients showed excellent results and 2 patients displayed good results regarding bone outcomes. When considering functional outcomes, 14 patients exhibited excellent results and 3 patients displayed good results. Conclusions: The muscle flap is synergistic with the Masquelet technique in the emergency management of severe complex fractures. The combination of both techniques in emergency surgery demonstrates an alternative option for the treatment of acute Gustilo type III trauma of the lower limb with segmental bone loss, which can effectively prevent bone infection and amputation. We also demonstrate that firm fixation is key to the Masquelet technique. Highlights: The muscle flap and Masquelet technique have synergistic effects in limb salvage for acute complex fractures in emergencies. The application of the Masquelet technique in emergencies can reduce postoperative complications of Gustilo type III trauma. Our study demonstrates that firm fixation is key to the success of the Masquelet technique.